Mild Palladium-Catalyzed C–H Alkylation Using Potassium Alkyltrifluoroborates in Combination with MnF3 - Neufeldt, Sharon R. (2013)
[Image: see text] A Pd-catalyzed method for ligand-directed C–H alkylation with organoboron reagents is described. The combination of potassium organotrifluoroborates, MnF(3), and a Pd(II) catalyst effects pyridine and amide-directed C–H alkylation. These reactions proceed under mild conditions (25–40 °C in weakly acidic media), are effective for installing methyl and 1° alkyl groups, and do not require promoters like benzoquinone.